Effect of Maturity Stage on the Gene Expression of Antioxidative Enzymes in Cucumber (Cucumis sativus L.) Fruits Under Chilling Stress - Chun-lu QIAN; Hong-bo MI; Yu-ying ZHAO; Zhi-ping HE; Lin-chun MAO (Journal of Integrative Agriculture, 2013)
The gene expression patterns of antioxidative enzymes in cucumber (Cucumis sativus L.) fruits at four different maturity stages, immature (3-8 d after anthesis (DAA), mature (9-16 DAA), breaker (17-22 DAA), and yellow (35-40 DAA), were determined before and after cold storage at 2°C for 9 d and after subsequent rewarming at 20°C for 2 d. The electrolyte leakage and malondialdehyde content in cucumber fruits were increased after cold storage and subsequent rewarming. Increased expressions of peroxidase, ascorbate peroxidase (APX), and monodehydroascorbate reductase after cold storage played an important role in cucumber fruits to cope with chilling injury. The elevated cyt-superoxide dismutase, catalase, APX and dehydroascorbate reductase after subsequent rewarming in cucumber fruits facilitated the recovery from chilling stress. The highest expression levels of all the seven antioxidative enzyme genes in yellow fruits might be responsible for the enhanced chilling tolerance. Cucumber fruits at earlier developmental stages was more susceptible to chilling stress than those at later stages. The relative higher gene expressions of antioxidative enzymes genes at earlier developmental stages may be the responses to the sever oxidative stress caused by chilling injury.